Performance Analysis YOLO11n Model for Chili Leaf Diseases Detection - Rayyan Nur Fauzan; Avirmed Enkhbat; Ervin Yohannes; Ricky Eka Putra (Universitas Negeri Surabaya, 2026)
Chili plants are a strategic agricultural commodity with high economic value, yet their production is often disrupted by disease attacks causing significant yield reduction. Early and accurate detection of chili leaf diseases is crucial for implementing precision agriculture practices. This research implements the YOLO11n (You Only Look Once version 11 nano) model for automated chili leaf disease detection using the